Embodied Readers: Teaching about the Earliest Christians in Rural Protestant America - Tina Shepardson (Journal for Interdisciplinary Biblical Studies, 2020)
This article discusses the ways in which my Introduction to the New Testament class at the University of Tennessee engages with and offers students tools for understanding and participating in social activism, particularly around race, ethnicity, gender identity, sexuality, and class. In recent years I have added new readings and class projects to the syllabus explicitly to encourage students to consider ways in which interpretations influence our conversations on LGBTQ+ rights, feminism, and racial and economic justice. In addition to covering the early history and context of the New Testament texts, my course teaches students to recognize how readers’ own embodied experiences affect their culturally contingent reading of these influential texts. The region of Appalachia is largely rural and economically depressed; deeply held conservative Protestant strains of Christianity pervade this “the Bible belt” region, and Donald Trump won Appalachia easily in the 2016 presidential election. A new wave of student activism has developed on campus in response to recent national events and to the concurrent rise in polarizing rhetoric in our country. I demonstrate here some of the concrete ways I am adapting my classroom teaching about the New Testament to engage with these urgent local, regional, national, and global conversations and the activism they are inspiring.